Editorial (Revista do Tribunal Regional Federal da 3ª Região, 2016)
In this issue of the Journal of the Federal Regional Court of the 3rd Region - the last under my tenure at the Journal's Office - I had the privilege of coordinating the preparation of special content in honor of the course recently promoted by EMAG on the New Code of Civil Procedure. In organizing this course, once again, EMAG's Board of Directors - chaired by Federal JudgeCecilia Mello - brought together renowned jurists to present theoretical and practical reflections on the new civil procedural legislation, making a major contribution to updating and improving the magistrates of the Federal Court of the 3rd Region. With this in mind, and with the aim of broadening the dissemination of the relevant issues debated, the Gabinete da Revista presents in this edition a collection of doctrinal articles written by the course's illustrious speakers. After all, at a time when the new legislation is coming into force, it is essential that all legal practitioners are prepared for a transition in the way the process is conducted, committed to cooperative action between procedural subjects that provides a swift and effective solution to conflicts beyond statistics. On this occasion, I would like to take this opportunity to thank all the civil servants and magistrates for their attention in reading the Journal and the case law selected in the editions coordinated by me, in the expectation that I have met the wishes of this Court.